Heat Transfer Enhancement Using Electrohydrodynamic and Magnetohydrodynamic Techniques: A Review - Mane, Nikhil S.; Hargude, Mukund L.; Mali, Mahesh (Asian Review of Mechanical Engineering, 2017)
Increasing heat transfer from heat exchangers using different active and passive techniques is main focus of many researchers. Heat transfer enhancement saves energy and decreases the size of heat transfer equipments and as heat transfer equipments are used in many industries the effect of these new techniques can be implemented at number of applications. The heat transfer enhancement is mostly concentrated in the area of extended surfaces but many new and innovative techniques are also emerging in the research. Electrohydrodynamics and Magneto hydrodynamics are the newly developed techniques which can be used to enhance the heat transfer in many processes. This paper provides a review on the use of electrohydrodynamic and magnetohydrodynamic techniques in heat transfer enhancement with their different accepts.